2010
DOI: 10.1111/j.1365-2052.2010.02095.x
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study for racing performances in Thoroughbreds clarifies a candidate region near the MSTN gene

Abstract: SummaryUsing 1400 microsatellites, a genome-wide association study (GWAS) was performed to identify genomic regions associated with lifetime earnings and performance ranks, as determined by the Japan Racing Association (JRA). The minimum heritability (h 2 ) was estimated at 7-8% based on the quantitative trait model, suggesting that the racing performance is heritable. Following GWAS with microsatellites, fine mapping led to identification of three SNPs on ECA18, namely, g.65809482T>C (P = 1.05E-18), g.6586860… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 21 publications
3
89
0
1
Order By: Relevance
“…Evaluation of retrospective racecourse performance, physical growth and stallion progeny performance has demonstrated that C/C and C/T horses are more likely to be physically precocious and enjoy greater racecourse success as 2-year-old racehorses than T/T horses 19,28 . These findings have been subsequently validated in three independent genome-wide association (GWA) studies 18,20,21 in populations of Thoroughbreds originating in Ireland, Great Britain, New Zealand 20 , USA 18 and Japan 21 . The singular, genomic influence on optimum race distance at the MSTN locus in the Thoroughbred is supported by a high heritability for race distance (h 2 = 0.94) 29 .…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Evaluation of retrospective racecourse performance, physical growth and stallion progeny performance has demonstrated that C/C and C/T horses are more likely to be physically precocious and enjoy greater racecourse success as 2-year-old racehorses than T/T horses 19,28 . These findings have been subsequently validated in three independent genome-wide association (GWA) studies 18,20,21 in populations of Thoroughbreds originating in Ireland, Great Britain, New Zealand 20 , USA 18 and Japan 21 . The singular, genomic influence on optimum race distance at the MSTN locus in the Thoroughbred is supported by a high heritability for race distance (h 2 = 0.94) 29 .…”
mentioning
confidence: 77%
“…Recently, variation at the MSTN locus has been found to be highly predictive of genetic potential for race distance aptitude in Thoroughbred racehorses [18][19][20][21] and contributes to morphological type in other horse breeds 22 . The MSTN locus is associated with muscle hypertrophy phenotypes in a range of mammalian species [23][24][25][26][27] and a single nucleotide polymorphism (SNP, g.66493737C/T) located in the first intron of the MSTN gene influences speed in the Thoroughbred 19 .…”
mentioning
confidence: 99%
“…For example, three noncoding polymorphisms around MSTN have been associated with racing capabilities in elite and common Thoroughbreds: (i) the g66493797T . C SNP at its first intron (Hill et al 2010a,b;Tozaki et al 2010), (ii) the insertion of a 227-bp-long short interspersed nuclear element (SINE) at its promoter (Hill et al 2010a), and (iii) the BIEC2-417495 SNP located 692 kb upstream of MSTN and 30 kb upstream of the glutaminase gene GLS (Binns et al 2010). In elite Thoroughbreds, homozygotes for the g66493797 C allele performed better in short (,1300 m) and fast races, heterozygotes in middle distance races (between 1301 and 1900 m), and homozygotes for the g66493797 T allele in long distance races (Hill et al 2010a,b).…”
Section: Engendering Modern Breedsmentioning
confidence: 99%
“…The advances in the genetic infrastructure for the horse has enabled the identification of a genomic region on ECA18 associated with racing performance phenotypes. Four case-control studies, including a candidate gene study [13], a microsatellite-based genome-wide association study [23], and two genome-wide SNP association studies [2,14] have identified the same genomic region on ECA18 as associated with racing performance phenotypes, including optimum race distance. In addition, a recent large-scale cohort study has demonstrated that the genomic region on ECA18 was associated with optimum race distance in Japanese Thoroughbred racehorses [24].…”
mentioning
confidence: 99%